2017
DOI: 10.1111/jpy.12596
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall physicochemical properties determine the thallus biomineralization pattern of Padina gymnospora (Phaeophyceae)

Abstract: Approximately half of the Padina (Dictyotales, Phaeophyceae) species mineralize aragonite needles over the adaxial thallus surface, where mineral bands are interspersed with nonmineralized regions along the thallus from the apical to basal end. However, this calcification pattern and the related algal properties are not well understood. Therefore, this work was performed to elucidate a potential role of cell walls in the inhibition/induction of mineralization in the brown alga Padina gymnospora. In a compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Feeding assays have also revealed that the methanolic extract (ME) of P. gymonospora was the most consumed by L. variegatus and contained low amounts of phlorotannins (PH). Our data showed that a low PH content in the P. gymnospora ME extract (0.23% ± 0.03 DW) used in feeding assays and from samples of the natural populations (0.11% ± 0.01 to 0.38% ± 0.02 DW) agree with the literature for tropical brown macroalgae (<0.5%) [35,46,47]. That said, these amounts are very low to inhibit herbivory [47].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Feeding assays have also revealed that the methanolic extract (ME) of P. gymonospora was the most consumed by L. variegatus and contained low amounts of phlorotannins (PH). Our data showed that a low PH content in the P. gymnospora ME extract (0.23% ± 0.03 DW) used in feeding assays and from samples of the natural populations (0.11% ± 0.01 to 0.38% ± 0.02 DW) agree with the literature for tropical brown macroalgae (<0.5%) [35,46,47]. That said, these amounts are very low to inhibit herbivory [47].…”
Section: Discussionsupporting
confidence: 88%
“…After collection, living macroalgal samples were stored in filtered seawater inside a dark isothermal chamber and transported to the laboratory. Thereafter, P. gymnospora individuals were maintained inside an 8 L aquarium with seawater enriched with Provasoli medium [63], under controlled conditions as already described elsewhere [35].…”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations